Multiphysics coupling between periodic gear mesh excitation and input/output fluctuating torques: Application to a roots vacuum pump. (29th September 2017) - Garambois, Pierre; Donnard, Guillaume; Rigaud, Emmanuel; Perret-Liaudet, Joël
Abstract: This paper presents the analysis of multiphysics coupling between periodic gear mesh excitation and upstream/downstream fluctuating loads using an iterative spectral methodology. This one is based on the resolution of the parametric equations of motion in the spectral domain. Its efficiency makes possible to treat both low and high frequency excitations for systems having a large number of degrees-of-freedom. The different excitation sources, the dynamic coupled equations of motion, the spectral methodology and the iterative resolution principle are described. The dynamic responses of a roots vacuum pump for which the spur gear high mesh frequency parametric excitation is coupled with a low fluidic drag torque frequency. The coupling between excitations generates a frequency enrichment of the dynamic response which is reflected on waterfall plots by emergence of numerous sidebands around harmonics of the mesh frequency.